Monopoly Theory Prior to Adam Smith: A Revision - Roover, Raymond De (Quarterly Journal of Economics, 1951)
First, I put downe for a Maxime that all Monapolies have bin condemned by all politique men and in all well governed Comonweales, as a cause of all dearth and scarcetie in the same, contrarie to the nature and kinde of all Societies, which first growe into Townes and Cities to lie in safetie and to leve in plentie and cheapnes. — A Discourse of Corporations (1587–89?). I. Introduction, 492. — II. The monopoly theory of the Doctors, 495. — III. Monopoly theory and economic policy, 501. — IV. Post-Scholastic monopoly theories, 508. — V. Conclusions, 522.